Hook plate fixation with versus without coracoclavicular reconstruction for distal clavicular fractures - Shuang Wu (Journal of Orthopaedic Surgery, 2022)
Purpose Hook plate fixation is one of the most frequently used methods for unstable distal clavicular fractures, but it is still unknown if there is a need for coracoclavicular (CC) reconstruction. This study aimed to compare the efficacy of hook plate fixation with versus without CC reconstruction for distal clavicular fractures. Methods Eighty-one patients who underwent hook plate fixation (HP group, n = 45) or hook plate fixation plus suture anchor reconstruction (HPA group, n = 36) for Neer type II or V clavicular fractures were enrolled. Demographics, fracture characteristics, and surgical data were recorded. Union time, coracoclavicular distance (CCD), post-operative complications, Constant score, and Disabilities of the Arm, Shoulder, and Hand (DASH) score were compared between HPA and HP groups. Results Constant score in the HPA group was higher than that in the HP group (91.8 ± 3.6 vs 88.8 ± 6.0, P = 0.007). However, there were no significant differences in union time, DASH score, CCD, and post-operative complications between the two groups (P > 0.05). Hook plate fixation combined with CC reconstruction costed more (3023.7 ± 202.6 vs 2416.2 ± 167.6 EUR, P < 0.001) and prolonged operative duration (78.2 ± 9.2 vs 73.7 ± 8.3 min, P = 0.023) compared with hook plate fixation alone. Conclusion Hook plate fixation with or without suture anchor reconstruction achieved satisfactory outcomes for Neer type II or V clavicular fractures. However, hook plate fixation plus CC reconstruction showed better functional outcomes compared with hook plate fixation alone.